2013
DOI: 10.1126/science.1231677
|View full text |Cite
|
Sign up to set email alerts
|

( R )-2-Hydroxyglutarate Is Sufficient to Promote Leukemogenesis and Its Effects Are Reversible

Abstract: IDH1 and IDH2 (Isocitrate Dehydrogenase 1 and 2) mutants are common in several cancers, including leukemias, and overproduce the (R)-enantiomer of 2-hydroxyglutarate [(R)-2-HG]. Elucidating the role of IDH mutations and (R)-2-HG in leukemogenesis has been hampered by a lack of appropriate cell-based models. Here we show that a canonical IDH1 mutant, IDH1 R132H, promotes cytokine-independence and blocks differentiation in hematopoietic cells. These effects can be recapitulated by (R)-2-HG, but not (S)-2-HG, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
610
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(642 citation statements)
references
References 31 publications
(36 reference statements)
25
610
1
6
Order By: Relevance
“…68 In addition, work is underway to identify specific inhibitors of mutated components of the epigenome, and such inhibitors are now in early-phase clinical trials. 69,70 The recent observation of the induction of cellular differentiation by an IDH1-mutant inhibitor in a refractory AML xenograft model and the candidacy of TET2 mutations as a predictive biomarker for response to hypomethylating agents in myelodysplastic syndromes (MDS) patients are also of some interest. 71,72 IMPACT OF PATIENT-RELATED FACTORS At present the very considerable advances in the understanding of the genomic landscape in MF appear not to have been validated sufficiently for adaptation in treatment algorithms to assess candidacy for allo-SCT compared to conventional therapy.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 99%
“…68 In addition, work is underway to identify specific inhibitors of mutated components of the epigenome, and such inhibitors are now in early-phase clinical trials. 69,70 The recent observation of the induction of cellular differentiation by an IDH1-mutant inhibitor in a refractory AML xenograft model and the candidacy of TET2 mutations as a predictive biomarker for response to hypomethylating agents in myelodysplastic syndromes (MDS) patients are also of some interest. 71,72 IMPACT OF PATIENT-RELATED FACTORS At present the very considerable advances in the understanding of the genomic landscape in MF appear not to have been validated sufficiently for adaptation in treatment algorithms to assess candidacy for allo-SCT compared to conventional therapy.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 99%
“…2HG accumulation competitively inhibits αKG-dependent dioxygenases, including histone demethylases and methylcytosine dioxygenases of the TET family that regulate cellular epigenetic status (12)(13)(14)(15). This epigenetic dysregulation is associated with impairment of cellular differentiation in multiple cell types, including hematopoietic cells (15)(16)(17)(18)(19)(20)(21). AGI-6780, a selective sulfonamide inhibitor of the mutant IDH2 enzyme, lowered 2HG levels and induced differentiation of TF-1 erythroleukemia cells and primary human AML cells harboring the IDH2 R140Q mutation (17), providing in vitro evidence that inhibition of the mutant IDH2 enzyme can reverse some of the phenotypic changes it induces.…”
Section: Introductionmentioning
confidence: 99%
“…Several theories have been proposed, Turcan et al (2012) reported that IDH mutations induces extensive DNA hypermethylation by remodeling the methylome to establish glioma hypermethylator phenotype which results in reorganization of the methylome and transcriptome (Turcan et al, 2012). In addition to this, it is also thought that IDH1/2 mutations prevent oxidative decarboxylation of isocitrate to α-ketoglutarate and confer novel enzymatic activity, facilitating the reduction of α-ketoglutarate to Table 2 2-hydroxyglutarate, a putative oncometabolite (Koivunen et al, 2012;Losman et al, 2013) and therefore IDH1 and IDH2 mutations are likely the integrally involved in the pathogenesis of malignant transformation (i.e., driver mutations) rather than epiphenomena. Nevertheless, elucidating the pathogenesis of IDH mutations will aid better understanding of the molecular mechanisms of gliomagenesis.…”
Section: Discussionmentioning
confidence: 99%